Genesis of dioctahedral K- and Na-bearing micas at the strongly altered Late Proterozoic unconformity of the Tandilia belt, central-eastern Argentina. - Martinez, Juan Cruz (2015)
The unconformity-related phyllosilicate mineral assemblages of the most pervasively alteredbasement of the Tandilia belt, central Buenos Aires Province, were studied from two ~50 km distant areas, Barker and San Manuel. The secondary dioctahedral K-white micas show a compositional spread probably by a solid-solution towards pyrophyllite. In addition, electron microprobe analyses of micas yielded widely variable Na* [Na/(Na+K+Ca+Ba)] ratios, which can be related to a compositional range between nearly pure muscovite and intermediate micas with maximum paragonite contents corresponding to muscovite55paragonite45 and muscovite40paragonite60 for the Barker and San Manuel areas, respectively. Scanning electron images suggest the local occurrence of paragonite/intermediate K-Na white micas, finely intergrown within secondary K-white mica and pyrophyllite. P-T pseudosections (H2O saturated) in the Na-K-Fe-Mg-Mn-Al-Si-Ti-O-H system for different XFe3+ (Fe+3/Fetot) constrain temperatures of formation of the secondary mineral assemblages around 280 - 340 ºC, whereas such mineral assemblages are almost insensitive to pressure between 0.5 and 5 kbar. At these P-T conditions, the most likely mineral assemblages include K-white mica, chloritoid, rutile, and hematite (± pyrophyllite ± paragonite). An additional phase is either quartz, which was observed as relic of the protolith, or diaspore. A 40Ar/39Ar step-heating age of 630 ± 30 Ma on a K-white mica rich sample linked the hydrothermal alteration event to the Brasiliano orogenic cycle.